Pharmacokinetic Parameters and Estimated Milk Withdrawal Intervals for Domestic Goats (Capra Aegagrus Hircus) After Administration of Single and Multiple Intravenous and Subcutaneous Doses of Flunixin Meglumine - Smith, Joe S.; Marmulak, Tara L.; Angelos, John A.; Lin, Zhoumeng; Rowe, Joan D.; Carlson, Jan L.; Shelver, Weilin L.; Lee, Elizabeth A.; Tell, Lisa A. (Frontiers in Veterinary Science, 2020)
Introduction: The study objectives were to estimate plasma flunixin (FLU) pharmacokinetic parameters and milk depletion profiles for FLU and its metabolite (5-hydroxy flunixin; 5-OH) after subcutaneous (SC) and intravenous (IV) administration of single and multiple flunixin meglumine (FM) doses to non-lactating (nulliparous and pregnant does) and lactating dairy goats. Analytical methods (ELISA and UPLC- MS/MS) for quantifying plasma FLU concentrations were compared. The final objective was to use regulatory (FDA and EMA) methods to estimate milk withdrawal intervals following extra-label drug use in goats. Methods: FM was administered IV and SC to commercial dairy goats at 1.1 mg/kg for single and multiple doses. Plasma and milk samples were analyzed for FLU and 5-OH via UPLC-MS/MS. Plasma samples were also analyzed for FLU concentrations via ELISA. Using statistical approaches recommended by regulatory agencies, milk withdrawal intervals were estimated following FM extra-label use. Results: Following IV administration of a single FM dose, clearances were 127, 199, and 365 mL/kg/hr for non-lactating (NL) pregnant does, NL nulliparous does, and lactating dairy does, respectively. Following multiple SC doses, clearance/F was 199 mL/kg/hr for lactating does. After IV administration of a single FM dose, terminal elimination half-lives were 4.08, 2.87, and 3.77 hr for NL pregnant does, NL nulliparous does, and lactating dairy does, respectively. After multiple SC doses, the terminal elimination half-life was 3.03 hr for lactating dairy does. No significant differences were noted for samples analyzed by UPLC-MS/MS or ELISA. Milk withdrawal intervals ranged from 36-60 hr depending on the regulatory statistical method and dosage regimen. Conclusions: Subcutaneous administration of FM to goats results in similar plasma pharmacokinetic parameters as IV administration. ELISA analysis is an alternative method to UPLC-MS/MS for quantifying FLU concentrations in caprine plasma samples. Following FM extra-label administration to dairy goats, clinicians could consider 36-60 hr milk withdrawal intervals.